Peptide foldamer-based inhibitors of the SARS-CoV-2 S protein-human ACE2 interaction - Violeta Marković; Jeelan Basha Shaik; Katarzyna Ożga; Agnieszka Ciesiołkiewicz; Juan Lizandra Perez; Ewa Rudzińska-Szostak; Łukasz Berlicki (Taylor & Francis Group, 2023)
The entry of the SARS-CoV-2 virus into a human host cell begins with the interaction between the viral spike protein (S protein) and human angiotensin-converting enzyme 2 (hACE2). Therefore, a possible strategy for the treatment of this infection is based on inhibiting the interaction of the two abovementioned proteins. Compounds that bind to the SARS-CoV-2 S protein at the interface with the alpha-1/alpha-2 helices of ACE2 PD Subdomain I are of particular interest. We present a stepwise optimisation of helical peptide foldamers containing trans-2-aminocylopentanecarboxylic acid residues as the folding-inducing unit. Four rounds of optimisation led to the discovery of an 18-amino-acid peptide with high affinity for the SARS-CoV-2 S protein (Kd = 650 nM) that inhibits this protein-protein interaction with IC50 = 1.3 µM. Circular dichroism and nuclear magnetic resonance studies indicated the helical conformation of this peptide in solution.